EVALUATION OF VOIP TRAFFICS OVER TIKRIT UNIVERSITY NETWORKS - Wisam Dawood Abdullah (Tikrit Journal of Pure Science)
In recent years, VoIP is a rapidly evolving technology that could possibly revolutionize the telecommunication industry. When implemented on wireless data networks, VoIP could prove to be instrumental in the convergence of existing fixed and cellular telephony networks with the fast growing wired and wireless data networks. Whereas, the growth of the VoIP applications with additional mobile devices in the institution of higher education and increasing number of users led to slow VoIP services. In addition, the throughput and latency (or delay, jitter, and jabber) are two of the most important issues that need to be resolved before the commercial deployment of wireless VoIP. The trace composes of two parts: firstly, collecting of data, secondly, performing the traffics analysis. Therefore, we have analyzed the performance offered by SCTP, TCP and UDP over VoIP at Tikrit University, Iraq. In this paper, we can see that the kind of performance given by SCTP is best then UDP, but the latency is decreased it performance significantly compared to UDP and the SCTP throughput is looks in a better manner. The measurements were verified by simulating the VoIP traffics using Network Simulator 2